Investigation of effective potential of electron-ion interaction in semibounded metal - Маркович, Б.; Markovych, B. (Lviv Politechnic Publishing House, 2018)
Подано чисельні розрахунки ефективного потенціалу електрон–іоної взаємодії в напівобмеженому металі (калії) з урахуванням поправки на локальне поле у формі Хаббарда з використанням локального псевдопотенціалу Красько–Гурського. Досліджено вплив поверхні поділу “метал–вакуум” та апроксимації для поправки на локальне поле на поведінку ефективного потенціалу електрон–іонної взаємодії.

The effective potential of the electron–ion interaction in a semibounded metal (potassium) is calculated numerically, taking into account the local field correction in the Hubbard form, using the local pseudopotential of Krasko–Gursky. The influence of the metal/vacuum interface and the approximation for the local field correction on the behavior of the effective potential of the electron–ion interaction is investigated.
Дослідження ефективного потенціалу електрон-іонної взаємодії в напівобмеженому металі
Keywords: ефективна електрон–іонна взаємодія; напівобмежений метал; поправка на локальне поле; effective electron–ion interaction; semibounded metal; local field correction; 530.145